Blockchain-based service publishing scheme with recommendation for cold start users - Xuewen DONG; Haozhe LIU; Hui QIAO; Jiawei ZHENG (Tongxin xuebao)
In order to solve the problem that the existing publishing systems were vulnerable to tampering, and it was difficult to recommend service information to “cold start” users, a blockchain-based service publishing scheme that supported cold-start user recommendations was proposed.The latent feature mapping model of a single auxiliary domain was extended to two auxiliary domains to make more accurate recommendations for cold start users in the target domain.In addition, the microservice architecture and block technology were combined to ensure system scalability, reliability and security.The experimental results of three real data sets extracted from Amazon transaction data show that the proposed recommendation model is better than most other recommendation methods, and the service release information can be safely stored in the blockchain to ensure that it is not changed.